1986
DOI: 10.1161/01.hyp.8.7.632
|View full text |Cite
|
Sign up to set email alerts
|

Plasma digitalislike activity in essential hypertension or end-stage renal disease.

Abstract: SUMMARY Plasma extracts from 119 subjects showed a digitalislike activity, as evidenced by the ability of these extracts to inhibit ouabain binding to the Na + -K + pump. High levels of the digitalislike compound were found in 18 of 54 untreated hypertensive subjects, 7 of 21 normotensive subjects with a family history of hypertension, and 10 of 14 patients with end-stage renal failure. Dialysis significantly reduced the activity of this compound. These results suggest 1) that endogenous digitalislike factor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Although several studies have shown a correlation between elevated endogenous cardiac glycosides and certain pathological conditions, the physiological function of endogenous cardiac glycoside-like compounds is still uncertain (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Plasma levels of endogenous cardiac glycosides are high in several animal models of hypertension, as well as in human essential hypertension and preeclampsia (10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have shown a correlation between elevated endogenous cardiac glycosides and certain pathological conditions, the physiological function of endogenous cardiac glycoside-like compounds is still uncertain (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Plasma levels of endogenous cardiac glycosides are high in several animal models of hypertension, as well as in human essential hypertension and preeclampsia (10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Plasma levels of endogenous cardiac glycosides are high in several animal models of hypertension, as well as in human essential hypertension and preeclampsia (10)(11)(12)(13)(14)(15)(16)(17). In addition, marked increases in endogenous ouabain-like compounds occur in congestive heart failure, both in animal models and human patients (18)(19)(20).…”
mentioning
confidence: 99%
“…Comparison is difficult because red cells were used as the target for plasma inhibitors and because of lack of information about heparin, and the time specimens were taken in relation to dialysis [27,29].…”
Section: Nak-atpase Inhibition Assaysmentioning
confidence: 99%
“…The identification of cardiac glycoside-like molecules in mammals has led to the proposal that these compounds are natural regulators of Na,K-ATPase in vivo (7)(8)(9)(10). Several studies have shown a correlation between these cardiac glycoside-like molecules and certain pathological conditions, such as hypertension and heart failure (11)(12)(13)(14)(15)(16)(17). Plasma levels of these putative ligands for the Na,KATPase are high in several animal hypertension models, as well as in human essential hypertension and preeclampsia (11-14, 18, 19).…”
mentioning
confidence: 99%